Assessing the impact of de facto trade globalization and regulatory quality on ecological footprint. Evidence from Japan (IITM Journal of Business Studies, 2024)
Japan is one of the developed nations in the Asian  continent and holds enormous geographical and  geopolitical importance in the cross-border  movement of goods, services, people, and  technology. Hence, it is substantial to analyse  the impact of its de facto trade globalization and  regulatory quality on ecological sustainability.  Therefore, the study employs the autoregressive  distributed lag (ARDL) model. Our results  confirm that de facto trade globalization and  regulatory quality have a positive impact  on environmental sustainability, whereas  economic growth has a negative impact on the  sustainability of the ecology. The results validate  that PHEH holds in Japan which means that  it promotes environmentally safe trade and  technology and its regulatory framework is  firm enough in promoting clean trade. The  relative decoupling situation is tantamount to  an environmentally conscious society with rising  economic performance
Keywords: trade globalization; regulatory; quality; ecological footprint; PHEH